2020
DOI: 10.3389/fpsyt.2020.00163
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics Underlying Susceptibility and Resilience Relating to Daily Life Stress, Work Stress, and Socioeconomic Status

Abstract: Susceptibility and resilience to mental disorders result from a complex choreography of gene-environment interactions with epigenetics at the intersection of external psychological stressors and internal biological systems. Increasing awareness of the growing disease burden influenced by daily life stress ("daily hassles"), work-related stress, and low socioeconomic status (SES) has resulted in a novel interest into their underlying molecular signatures. This review offers a brief outline of psychiatric epigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 53 publications
1
30
0
1
Order By: Relevance
“…In contrast to neuroticism, our unpublished data has shown that resilience may improve work stressors and subsequent stress responses. Previous studies reported a buffering effect of resilience on job stressors (23)(24)(25)(26)(27)(28)(29)(30). However, to our knowledge, there has been no study to date that analyzed the association between parenting, resilience, and stress responses among general workers.…”
Section: Introductionmentioning
confidence: 97%
“…In contrast to neuroticism, our unpublished data has shown that resilience may improve work stressors and subsequent stress responses. Previous studies reported a buffering effect of resilience on job stressors (23)(24)(25)(26)(27)(28)(29)(30). However, to our knowledge, there has been no study to date that analyzed the association between parenting, resilience, and stress responses among general workers.…”
Section: Introductionmentioning
confidence: 97%
“…Despite the limitations, our findings from a general population sample of adolescents and young adults emphasize the focus on DH and recent chronic stress in a GxE framework, which is in line with other studies also pointing towards the influence of DH on anxiety (Barrett & Heubeck, 2000; D'Angelo & Wierzbicki, 2003). In further studies, additional factors like epigenetic processes modulating gene function and temporally dynamic processes susceptible to environmental influences, such as daily life stress respect to anxiety (for a review see Gottschalk et al, 2020; Schiele & Domschke, 2018) in particular SLC6A4 DNA methylation (Domschke et al, 2014; Duman & Canli, 2015; Kang et al, 2013; Roberts et al, 2014; Schiele, Kollert et al, 2019) have to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, studies of resilience have expanded beyond merely describing individual characteristics to focusing on the ‘complex choreography’ (Gottschalk 2020 ) between individuals and their changing personal and environmental contexts. Recent data have shown that resilience is best understood as a continuum with the potential to change across a lifespan based on biological, developmental and cultural determinants as well as evidence-based interventions and deliberate practice on the part of the individual.…”
Section: Learning Objectivesmentioning
confidence: 99%
“…Certain environmental exposures throughout the lifespan, such as maternal care, social support and drug use, have been found to alter chromatin structure, thus affecting gene expression and an individual's susceptibility to trauma (Dudley 2011 ). In studies of adults, differences in methylation patterns of candidate genes, for example the serotonin transporter gene ( SLC6A4 ) promoter, have been linked with differential psychological outcomes related to stressors of various degrees (Gottschalk 2020 ), as well as differential limbic system activity in response to sad and fearful stimuli (Ismaylova 2018 ).…”
Section: Neurobiology and Stressmentioning
confidence: 99%